Study of Working Experience in Remote Rural Areas after Medical Graduation - Thapa, KR; Shrestha, BK; Bhattarai, MD (Kathmandu University Medical Journal, 2015)
Background Posting of doctors in remote rural areas has always been a priority for Government; however data are scarce in the country about experience of doctors of working in remote areas after medical graduation. Objective A questionnaire survey of doctors was planned to analyze their experience of working after graduation in remote rural areas in various parts of the country. Method The cross-sectional survey was done by convenience sampling method. A one-page questionnaire with one partially closed-end and five open-end type questions was distributed to the doctors who had worked in remote rural areas after graduation under various governments’ postings. Result Two-third of participants had their home in urban areas and 89.8% had stayed for 1 to 5 years. About half of the participants had difficulty in getting the posting in the remote areas of their choice. Most participants indicated provision of opportunities for Residential (postgraduate) Training as their reasons of going to remote areas as well as their suggestions to encourage young graduates to go there. Similarly most also suggested appropriate career, salary and incentives to encourage doctors to go to work in remote areas. About 85% of participants pointed out the major problem faced while posted in remote areas as difficulty in handling varied situations with no guidance or seniors available around. Conclusion The notable points indicated by the participants are centered on the opportunity for Residential Training and difficulties faced without such training. Residential Training is a priority to be considered while planning the health policy for optimum health care of people. Kathmandu University Medical Journal Vol.12(2) 2014: 121-125